2004
DOI: 10.1080/07853890410031236
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y and Y2‐receptor are involved in development of diabetic retinopathy and retinal neovascularization

Abstract: NPY and Y2-receptor play important roles in diabetic retinopathy and retinal neovascularization and are thus potential new targets for drug molecules for treatment of retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 20 publications
3
52
0
Order By: Relevance
“…Interestingly, the polymorphism exists with a relatively high frequency in Finnish and Swedish populations but low frequency in other ethnic populations (18,19). In the past 7 years, several genetic studies indicate that polymorphism is associated with the development of T2D (20), retinopathy (21,22), and enhanced carotid atherosclerosis (23). Moreover, there is a report indicating that Leu7Pro polymorphism confers susceptibility to the development of nephropathy and coronary heart disease (CHD) in Finnish female T1D patients (24).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the polymorphism exists with a relatively high frequency in Finnish and Swedish populations but low frequency in other ethnic populations (18,19). In the past 7 years, several genetic studies indicate that polymorphism is associated with the development of T2D (20), retinopathy (21,22), and enhanced carotid atherosclerosis (23). Moreover, there is a report indicating that Leu7Pro polymorphism confers susceptibility to the development of nephropathy and coronary heart disease (CHD) in Finnish female T1D patients (24).…”
Section: Introductionmentioning
confidence: 99%
“…NPY has been reported to directly stimulate endothelial cell proliferation and migration (Ekstrand et al, 2003;Ghersi et al, 2001;MarionAudibert et al, 2000;Zukowska-Grojec et al, 1998a,b). In the retina, some evidences have shown that NPY and Y 2 receptors are involved in development of diabetic retinopathy and retinal neovascularization (Koulu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The results are in accordance with a recent report in Swedish men (Nordman et al, 2005) although in the present study the association was positive in both sexes. PreproNPY Leu7Pro polymorphism has been linked to accelerated atherosclerosis (Niskanen et al, 2000a) and progression of diabetic retinopathy (Niskanen et al, 2000b;Koulu et al, 2004) in type II diabetic subjects. Some studies have also related the Leu7Pro polymorphism with decreased insulin secretion (Jaakkola et al, 2005) and lower free fatty acid levels both in the fasting state and during the hyperinsulinemic clamp (Pihlajamäki et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…NPY is, therefore, a good candidate gene for type II diabetes. The functional leucine 7 to proline (Leu7Pro) polymorphism in the signal peptide of NPY has been earlier associated with plasma NPY levels (Kallio et al, 2001(Kallio et al, , 2003, insulin metabolism (Kallio et al, 2003;Jaakkola et al, 2005), type II diabetes (Nordman et al, 2005) and its complications (Niskanen et al, 2000a, b;Koulu et al, 2004). The results have been, however, contradictory, and the mechanisms behind these associations largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation